Xanthoma Disseminatum with Tumor-Like Lesion on Face - Habib Ansarin; Hoda Berenji Ardestani; Seyed Mehdi Tabaie; Nasrin Shayanfar (Case Reports in Dermatological Medicine)
Xanthoma disseminatum (XD) is a rare benign mucocutaneous xanthomatosis that is classified as a benign non-Langerhans cell histiocytosis. We report a 62-year-old man who presented with widespread yellow-brown papulonodular and tumoral lesions on face, flexors, and trunk. Histopathological features of the cutaneous lesions were typical of XD.